PERSEPSI MASYARAKAT TENTANG IMUNISASI MR PUSKESMAS GLUGUR DARAT KECAMATAN MEDAN TIMUR 2019 - Eva Latifah Nurhayati; Debi Novita Siregar (Universitas Medan Area, 2020)
This study aims to find out how people's perceptions about MR immunization, as for the background of this research is because in the community there are many pros and cons in the implementation of MR immunization. This research is quantitative with a case study in Glugur Darat Health Center. The population is the community that has children aged 9 months to 15 years. Determination of the sample with quota sampling. With a total sample of 100 people. Data collection instruments with documentation, questionnaires and direct interviews which are then analyzed using simple linear correlation. From the results of this study indicate the public perception of MR Immunization in the Work Area of the Glugur Darat Health Center the majority of 71% do not understand about MR immunization. And from the results of the chi quare test to analyze the relationship between the perception of the community about MR immunization and the participation of MR immunization, the results obtained p = 0,000. Then there is a relationship between the public perception of MR immunization with the participation of MR immunization. For onshore glugur health centers to provide information to the public about MR immunization by providing counseling to the community, distributing leaflets about MR immunization.